2009
DOI: 10.1523/jneurosci.5505-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Protect Neurons against Ischemia by Synthesis of Tumor Necrosis Factor

Abstract: Microglia and infiltrating leukocytes are considered major producers of tumor necrosis factor (TNF), which is a crucial player in cerebral ischemia and brain inflammation. We have identified a neuroprotective role for microglial-derived TNF in cerebral ischemia in mice. We show that cortical infarction and behavioral deficit are significantly exacerbated in TNF-knock-out (KO) mice compared with wild-type mice. By using in situ hybridization, immunohistochemistry, and green fluorescent protein bone marrow (BM)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
355
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(377 citation statements)
references
References 64 publications
17
355
1
4
Order By: Relevance
“…Microglia activation and TNF release are associated with cell death and pathological inflammation, but they are also implicated in immune tolerance and brain repair. Removing TNF may not be fully beneficial, as this strategy has only had limited success 7,11-14 and TNF-deficient mice appear to have exacerbated cortical infarction and behavioural deficit 41 . One of the ARTICLE underlying reasons may be that a reduction in the homoeostatic levels of TNF may affect neuronal survival 6,12 .…”
Section: Discussionmentioning
confidence: 99%
“…Microglia activation and TNF release are associated with cell death and pathological inflammation, but they are also implicated in immune tolerance and brain repair. Removing TNF may not be fully beneficial, as this strategy has only had limited success 7,11-14 and TNF-deficient mice appear to have exacerbated cortical infarction and behavioural deficit 41 . One of the ARTICLE underlying reasons may be that a reduction in the homoeostatic levels of TNF may affect neuronal survival 6,12 .…”
Section: Discussionmentioning
confidence: 99%
“…CA/CPR-induced neurological damage is a progressive process that can develop over a long time following the initial injury (15). As aforementioned, strong evidence now exists to suggest that neuroinflammation continues for days and months, and contributes to the neurological damage that ultimately determines the impaired recovery following CA and CPR (16). This suggests that the neuroprotective anti-inflammatory treatments discussed in the following are promising strategies for CA and resuscitation intervention.…”
Section: Development Of Neuroprotective Interventions Following Ca Anmentioning
confidence: 93%
“…Despite a more comprehensive understanding regarding the mechanisms of cerebral injury, currently no clinically proven pharmacological therapy data against cerebral I/R damage during CA and CPR are available (15). Increasing evidence reveals that suppressing the inflammatory process facilitates neuroprotection and has potential for use in the clinical treatment of cerebral I/R damage regarding CA (16).…”
Section: Inflammatory Mechanisms Involved In Brain Injury Following Cmentioning
confidence: 99%
“…In particular, TNF-α play a beneficial role in neurogenesis after ischemic injury, probably acting via its receptor TNF-R2, promoting the survival of strokegenerated hippocampal and striatal neurons (Heldmann et al, 2005). Interestingly, it has been shown that TNFα knockout mice have a 50% increase in the final ischemic damage (Lambertsen et al, 2009). Microglial activation in the perilesional area might also positively regulate post-stroke neurogenesis by increasing the expression of the neuroprotective mediator IGF-1 in the SVZ (Thored et al, 2009).…”
Section: Reparative Regenerationmentioning
confidence: 99%